FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA - Elania, Nurul; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTHigh competition in business world has forced companies to have competitive advantage to keep on competing. Whether the corporate performance is good or bad it will give an impact to the firm value and it can give influence to the interest of investors to invest their capital in the company. This research is meant to examine some factors i.e. financial laverage, net profit margin, return on assetsandfirm size which give influence to the smoothing income. Smoothing income is measured by using eckel index calculation. This research is quantitative research. The population is all manufacturing companies which are listed in Indonesia Stock Exchange in 2013-2015 periods. The sample selection has been done by using purposive sampling technique and 65 companies which have meet the criteria have been selected as samples so 195 observations have been obtained. The data analysis technique has been carried out by using multiple regression and SPSS program 20th version. Based on the result of the examination, it can be concluded that Debt to Equity Ratio gives positive influence to the smoothing income, Net Profit Margin does not give any positive influence to the smoothing income, Return on Assets does not give any positive influence to the smoothing income, and firm size does not give any positive influence to the smoothing income.Keywords: Smoothing Income, Financial Leverage, Profitabiliy, Firm Size.